The Influence of Leadership and Emotional Intelligence on Employee Performance through Work Stress at PT. NIC Makassar - Akhmad Akhmad; Djabir Hamzah; Muhammad Toaha (Hasanuddin Journal of Applied Business and Entrepreneurship, 2022)
Human Resources as an important asset of a company must be managed so that employees are optimal in achieving their performance. This study aims to determine the effect of leadership, emotional intelligence on employee performance mediated by job stress at PT. NIC Makassar. This study uses a quantitative method with a population of 315 employees. The research sample is 100 employees, a working period of more than 2 years, the level of Operator-Supervisor position. Data collection techniques in this study were questionnaires, observation, and documentation. The data analysis technique in this study used Partial Least Square (PLS). The results showed that (1) there was a positive and significant effect between leadership on employee performance at PT. NIC. (2) there is a positive and significant effect between emotional intelligence on employee performance at PT. NIC (3) there is a significant negative effect between work stress on employee performance at PT. NIC. (4) there is a negative influence of leadership on employee work stress at PT. NIC. (5) there is an effect of emotional intelligence on the work stress of employees of PT. NIC.(6) there is an indirect effect of leadership on employee performance through the work stress of employees of PT. NIC. (7) there is an indirect effect of emotional intelligence on employee performance through work stress of employees of PT. NIC.